The Role of Wind Turbine Siting in Achieving Sustainable Energy Goals - Duranay, Zeynep Bala; Guldemir, Hanifi; Coskun, Bilal (Mdpi, 2024)
As global energy demands rise, there is an increasing need to transition from fossil fuels, which contribute to environmental harm and have limited reserves, to more sustainable and renewable energy sources. This shift is vital for both protecting the environment and ensuring long-term energy security. Renewable energy, such as wind power, plays a significant role in mitigating climate change and reducing greenhouse gas emissions while also being environmentally harmonious. Wind energy, in particular, is gaining importance as a clean, renewable source of power, with wind turbines serving as key components of this transformation. The success of wind energy projects depends largely on proper site selection. Factors such as wind potential, the topographical structure, environmental sensitivity, and legal considerations must all be carefully analyzed to ensure maximum performance and minimal environmental impact. The site selection process is crucial in optimizing energy production while promoting sustainability. Effective micro-siting strategies, which focus on the specific placement of turbines within a site, are also essential for improving energy efficiency and minimizing environmental disruption. This study highlights the importance of careful site analysis to ensure the successful and sustainable implementation of wind energy projects.
Keywords: renewable energy; site selection of wind turbines; sustainability; wind energy; wind turbines